Catalyzing progress: Unveiling the impact of metallic improved cooking stoves on energy security and sustainable development - Amir Budhathoki; Chomsri Choochuay; Shital Bhandary (Heliyon)
The global energy crisis, characterized by shortages of fossil fuels, increasing energy needs, and climate change, requires sustainable energy solutions. Renewable energy technologies provide important options to reduce GHG emission and improve energy security. In developing nations, the use of traditional biomass-fueled cooking stoves contributes to environmental damage, deforestation, and health problems. This research evaluates the impact of MICS on Energy Security and Sustainable Development in Bajura District, Nepal, where firewood is the main source of cooking and heating fuel. Employing an Explanatory Sequential Research Design, the study integrated quantitative survey followed by qualitative approach. A household survey was carried out using KoBo Toolbox among 507 households, followed by focus group discussion and in-depth interviews among 63 people. Survey data was analyzed in SPSS to see the impacts of MICS usage. Findings demonstrated significant reduction of firewood by 693.78 tons (33.85 %) and CO2 emissions by 1247.4 tons (60.93 %) per annum improving energy security, and positive socio-economic and environmental impacts. Research emphasizes the significance of MICS on Energy Security and SD, offering valuable insights for decision-makers. Despite the benefits of MICS, only 44 % of households had adopted them due to high costs, lack of awareness, and maintenance challenges as barriers, advocating for policies to increase adoption through subsidies, awareness campaign, and maintenance assistance as 94.5 % of the surveyed population still use firewood for cooking and heating.